Structurally engineered cobalt−iron layered double hydroxide on metal organic framework electrocatalyst for enhanced electrocatalytic water splitting performance - Yasir Hashmi; Jianzhi Wang; Faquan Yu (Macedonian Journal of Chemistry and Chemical Engineering)
Metal-organic frameworks (MOFs) have garnered significant attention as potential electrocatalysts. However, their direct application as bifunctional catalysts for overall water splitting remains challenging. In this study, we successfully synthesized a three-layered cobalt-iron layered double hydroxide (CoFe-LDH) on a MOF (CoFe-MOF) hybrid electrode (CoFe-LDH@CoFe-MOF/Co/CC) using a simple solvothermal method. Based on electrochemical analysis, this electrode exhibits remarkable electrocatalytic performance, requiring a low overpotential of 365 mV at 50 mA/cm2 for the oxygen evolution reaction (OER). The outstanding catalytic performance is attributed to the unique hierarchical structure and the synergistic effect between CoFe-LDH and CoFe-MOF. Additionally, electrochemical testing suggests that other species formed during the reaction contribute to the enhanced activity of this material. Our findings offer valuable insights into the rational design of MOF-based electrocatalysts for efficient water splitting applications.